2020
DOI: 10.1016/j.scitotenv.2020.140935
|View full text |Cite
|
Sign up to set email alerts
|

Containing the spread of coronavirus disease 2019 (COVID-19): Meteorological factors and control strategies

Abstract: The novel coronavirus disease 2019 (COVID-19) has spread globally and the meteorological factors vary greatly across the world. Understanding the effect of meteorological factors and control strategies on COVID-19 transmission is critical to contain the epidemic. Using individual-level data in mainland China, Hong Kong, and Singapore, and the number of confirmed cases in other regions, we explore the effect of temperature, relative humidity, and control measures on the spread of COVID-19. We find that high tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 19 publications
5
56
1
2
Order By: Relevance
“…Equation (9a), however stresses that temperature and humidity are of secondary relevance to the virus spread rate, since they are inter-regime influences, rather than intra-regime ones. The very existence of this relevance (together with its being of limited or secondary nature only) seems to be in line with the reported disparity among the cited references [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Qualitative reasoning [30, [35][36][37] show that, according to (9a), temperature and humidity have opposing influences on virus spread rate.…”
Section: Derivation Of the Virus Spread Rate Via The Dimensional Basissupporting
confidence: 68%
See 1 more Smart Citation
“…Equation (9a), however stresses that temperature and humidity are of secondary relevance to the virus spread rate, since they are inter-regime influences, rather than intra-regime ones. The very existence of this relevance (together with its being of limited or secondary nature only) seems to be in line with the reported disparity among the cited references [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Qualitative reasoning [30, [35][36][37] show that, according to (9a), temperature and humidity have opposing influences on virus spread rate.…”
Section: Derivation Of the Virus Spread Rate Via The Dimensional Basissupporting
confidence: 68%
“…We stress that most papers surveyed stress that both temperature and humidity are of some relevance (that cannot be neglected) to the spread rate for coronaviruses, in general (and for the novel coronavirus, in particular) [38][39][40][41][42][43][44][45][46][47][48][49]. A notable exception to the general trend in the papers surveyed is the work of Jamil et al [50], who tested the hypothesis that COVID-19 spread is temperature-dependent using data derived from nations across the world and provinces in China, and found no evidence of a pattern between spread rates and ambient temperature, suggesting that the SARS-CoV-2 is unlikely to behave as a seasonal respiratory virus.…”
Section: Derivation Of the Virus Spread Rate Via The Dimensional Basismentioning
confidence: 99%
“… ƞahin (2020) also assessed the impact of weather on the COVID-19 pandemic in Turkey pointing out that that wind speed 14 days prior to and the temperature of the day of the study yielded higher numbers of cases. Similarly, Lin et al (2020) identified that meteorological parameters influence COVID-19 as daily maximal temperature, wind speed and air pressure are inversely correlated with reproductive ratios. Furthermore, Tang et al (2020) explored the correlation between the average percent of positive COVID-19 in the USA and dosages of sunlight ultraviolet radiation.…”
Section: Resultsmentioning
confidence: 97%
“… Wu et al (2020) likewise report that a 1% increase in relative humidity can be linked with a 0.85% decrease in new daily cases and a 0.51% increase with a reduction of new daily deaths. Lin et al (2020) further assessed the interaction of temperature and relative humidity and their effects on the spread of the virus. Their findings indicate that high relative humidity promotes COVID-19 transmission when temperatures are low, but tends to reduce transmission when the temperatures are high.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have proposed that viruses (bacteriophages) survived well at RHs lower than 33% and at 100%, whereas their viability was significantly decayed at 55% and 75% RHs [168] . However, SARS-CoV-2 may be resistant to high temperatures and intermediate RH [169] . Found in a cluster-spreading event investigation, a patient with SARS-CoV-2 may have transmitted the virus even with temperatures from 25 to 41 °C and humidity of approximately 60% [170] .…”
Section: Characteristics Of Coronaviruses In Aerosol and Inanimate Sumentioning
confidence: 99%